2004
DOI: 10.1093/jnci/djh287
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight and Risk for Childhood Leukemia in Denmark, Sweden, Norway, and Iceland

Abstract: Our results are compatible with the hypothesis that a high birth weight is associated with an increased risk of ALL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
148
3
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(159 citation statements)
references
References 46 publications
4
148
3
4
Order By: Relevance
“…Rather, AML was associated with both low birth weight and high birth weight. The U-shaped dose -response curve for birth weight and AML was also reported in a recent large study from Scandinavia (Hjalgrim et al, 2004). Most studies that have reported on AML and birth weight in ordinal categories have not yielded similar results (Shu et al, 1988;Ross et al, 1997;Yeazel et al, 1997;Shu et al, 1999;Reynolds et al, 2002;Jourdan-Da Silva et al, 2004), although several used relatively high cutoffs (2700 or 3000 g) for the lowest birth weight category (Shu et al, 1988;Ross et al, 1997;Yeazel et al, 1997;Shu et al, 1999).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Rather, AML was associated with both low birth weight and high birth weight. The U-shaped dose -response curve for birth weight and AML was also reported in a recent large study from Scandinavia (Hjalgrim et al, 2004). Most studies that have reported on AML and birth weight in ordinal categories have not yielded similar results (Shu et al, 1988;Ross et al, 1997;Yeazel et al, 1997;Shu et al, 1999;Reynolds et al, 2002;Jourdan-Da Silva et al, 2004), although several used relatively high cutoffs (2700 or 3000 g) for the lowest birth weight category (Shu et al, 1988;Ross et al, 1997;Yeazel et al, 1997;Shu et al, 1999).…”
Section: Discussionmentioning
confidence: 68%
“…In addition, risk increased 14% with each 1000 g increase in birth weight. While some studies have been negative (Robison et al, 1987;Kaye et al, 1991;Savitz and Ananth, 1994;Dockerty et al, 1999;Thompson et al, 2001;Ma et al, 2005), the majority of studies support a weak to moderate increased risk of ALL among children who had heavier birth weights (Buckley et al, 1994;Cnattingius et al, 1995;Ross et al, 1997;Westergaard et al, 1997;Yeazel et al, 1997;Smulevich et al, 1999;Suminoe et al, 1999;Murray et al, 2002;Okcu et al, 2002;Reynolds et al, 2002;Shu et al, 2002), including some studies published since the metaanalysis (Hjalgrim et al, 2004;Jourdan-Da Silva et al, 2004;Lee et al, 2004;Paltiel et al, 2004). Our findings with respect to birth weight are consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…High birth weight, low gestational age and certain in utero exposures have all been related to the risk of ALL, but it is not known whether they exert their effects by being risk factors for the development of preleukemic cells in an otherwise healthy fetus. 8,10,11 Similarly, the postnatal exposures that eventually may induce ALL in children harboring preleukemic cells remain to be determined, but among others they seem to correlate with high socioeconomic standards, including a delay in infectious exposures in early childhood (for a review see McNally and Eden 12 ). This has been supported by studies of the incidence of ALL (and phenotypic subtypes) in countries with high versus low socioeconomic status, cluster analyses, studies of population mixing, mapping of infection patterns in case-control studies and by genetic studies that have linked the risk of ALL to certain alleles of polymorphic genes that affect responses to infections.…”
mentioning
confidence: 99%
“…This explanation seems unlikely given the quantity of these studies. 8,[10][11][12][13][14][15] Why, then did the recent large population-and register-based Nordic study indicate that the risk of childhood is not increased in siblings to children with ALL and perhaps even reduced? 1 Both the presence of preleukemic cells at birth and the appropriate genetic predisposition and postnatal environment are believed to be necessary for the development of childhood ALL in the age peak group.…”
mentioning
confidence: 99%
“…This possible association has been studied for melanoma (Andersson et al, 2001;McCormack et al, 2005;Ahlgren et al, 2007) and other types of cancer (Le Marchand et al, 1988;Tibblin et al, 1995;Roman et al, 1997;Wanderås et al, 1998;Vatten et al, 2002;Hjalgrim et al, 2004;Nilsen et al, 2005;Michos et al, 2007). The results are inconclusive; however, there seems to be an association between birth weight and the risk for some cancer forms.…”
mentioning
confidence: 99%